STRATEGI PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN BERDASARKAN PERSEPSI MASYARAKAT DI DESA DAYUN KABUPATEN SIAK - Dolly Kuswara Harahap; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the strategy for the prevention of forest fires and land based on public perception in the village of Dayun Siak district. The method used in this research is purposive sampling method. Data analysis using analysis of percentage and SWOT analysis. The result showed that the forest fires and land frequently occur are influenced by social conditions like cultural society that opening land by burning which is still often done and majority of people’s livelihoods as farmers. Forest fire prevention effort and land that has been done by the people of the village of Dayun which is liaising with the parties or institutions in the prevention of forest fires and land. Based on the SWOT analysis, strategies prevention of the forest fires and land based on public perception is improving the skills of community through community care of fire, improving the facilities and infrastructure of the forest and land fires prevention for communities and strict law enforcement to arsonists forest and land.Keywords: Perception, Prevention, Forest fire and land